The use of thinking based learning strategies with young learners through storytelling in the EFL classroom - González López, Arianna autor; Castro Carracedo, Juan Manuel, 1976- (2024)
A great number of new methodologies for teaching English to young learners have been implemented in education. No doubt all moving away from old traditional styles, where learning English as a foreign language was often a teacher-centered approach. These current active methodologies on the other hand are focused on a student-centered approach, where students become participants of their own learning. Not only making students autonomous of their learning and but converting teachers into guides that help students´ in their learning process. Based on this current reality, this dissertation will firstly discuss the role of critical thinking in education and more specifically it will focus on Robert Swartz´s Thinking based Learning active methodology, which aims to help learners with critical and creative thinking. Its use in an EFL classroom creates a great learning environment for not only thinking skills but also the acquisition of a second language in a meaningful manner.